Hydrogeological critical settings for stability of river-banks: the case of the Pioverna River (Valsassina, Lecco, Italy) - Colombo, Loris; Francani, Vincenzo; Cremonesi, Daniele (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"Background knowledges about inundation phenomena in Lombardy (Italy) demonstrates that the behavior of rivers during the oods is characterized by high erosion capacity, especially in Alpine and Prealpine Valleys.The purpose of this study is to verify if riverbank instability can be enhanced by hydrogeological causes in addition to erosion due to the high stream speed.These events happen during ash oods, which are characterized by quick high increases in water surface variations, followed by rapid decreases to the previous conditions.In this paper also are presented studies about landslides, which are caused, during oods, not only by ow velocity, but also by increasing of hydraulic gradients of the aquifer connected to the river.In these conditions it is possible to have both piping, characterized by removal of ne sediments, and, sometimes, terrain liquefaction.Another purpose of this study is to nd criteria to identify the geological settings most subjected to instability, in order to facilitate prevention of riverbank landslides."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">Background knowledges about inundation phenomena in Lombardy (Italy) demonstrates that the behavior of rivers during the oods is characterized by high erosion capacity, especially in Alpine and Prealpine Valleys.The purpose of this study is to verify if riverbank instability can be enhanced by hydrogeological causes in addition to erosion due to the high stream speed.These events happen during ash oods, which are characterized by quick high increases in water surface variations, followed by rapid decreases to the previous conditions.In this paper also are presented studies about landslides, which are caused, during oods, not only by ow velocity, but also by increasing of hydraulic gradients of the aquifer connected to the river.In these conditions it is possible to have both piping, characterized by removal of ne sediments, and, sometimes, terrain liquefaction.Another purpose of this study is to nd criteria to identify the geological settings most subjected to instability, in order to facilitate prevention of riverbank landslides.